BK virus-associated hemorrhagic cystitis in pediatric stem cell transplantation: a case report and scoping review - Moss, Julia E.; Muller, William J. (Frontiers in Pediatrics, 2024)
Introduction: BK virus-associated hemorrhagic cystitis (BK-HC) is a debilitating and poorly understood complication of hematopoietic stem cell transplantation (SCT). Hematuria, dysuria, and other symptoms associated with BK-HC are common in the immediate post-SCT period, making BK-HC difficult to distinguish from other conditions presenting with these symptoms. Despite published criteria for diagnosis, the degree to which these criteria are consistently applied to either clinical diagnosis or to studies informing BK-HC management is unclear. We present a case of BK-HC in a pediatric SCT recipient, and discuss the challenges associated with treatment in the absence of rigorous data to inform clinical management.Methods: We reviewed all cases of BK viruria at our center in patients undergoing SCT between January 2015 and December 2019. We then performed a scoping review of publications in PubMed addressing BK-HC, specifically focusing on how BK-HC was defined. Publications using the keywords "BK polyomavirus" and "hemorrhagic cystitis" were included if they involved a clinical study of SCT recipients and a full-text article was available in English. Case reports were excluded. Analysis focused on whether BK-HC was explicitly defined and whether the definition incorporated elements of diagnostic criteria published by European Conference on Infections in Leukemia (ECIL).Results: A total of 30 studies published between January 2018 and June 30, 2021 met criteria for review, including 4 clinical trials, 7 prospective observational studies, and 19 retrospective observational studies. Fifteen of these studies included pediatric patients (7 pediatric only, 8 combined adult and pediatric). Of the 30 publications, 19 included a definition of either BK-HC or BK cystitis, with only five using ECIL criteria, all of which were observational studies. Multiple interventions are described for treatment of BK-HC, including cidofovir, leflunomide, quinolones, hyperbaric oxygen, keratinocyte growth factor, and BK-specific cytotoxic T lymphocytes. However, evidence to support efficacy for any of these interventions is lacking.Discussion: Although BK-HC is a well-known complication of SCT, evidence to support available treatment options is limited. Well-controlled studies that incorporate clear diagnostic criteria are needed to better define the risk factors, natural history, and ideal interventions.